Effect of seed priming and foliar application of organic liquid manure on germination, growth, yield and quality of late-sown wheat - Okram Ricky Devi; Omvati Verma; Bibek Laishram; S. Anbarasan; Abhijit Debnath; Narinder Panotra; Priyanka Elumle; Sunita T. Pandey; R. Ajaykumar; Samreen (Emirates Journal of Food and Agriculture)
The sub-optimal temperature during sowing results in delayed germination, poor crop establishment, and constrained vegetative development, which results in forced maturity, low yield, and wheat with poorer quality grains in north India. Thus, in 2020–21, a field experiment with fixed plots was carried out to analyze the impact of organic liquid manure herbal kunapajala as seed priming and foliar spray on the development and output of late-sown wheat. A total of 14 different treatments were tested in this thrice-replicated randomized block design study. Treatments consisted of T1 :No seed priming + 100% RDN, T2: Hydropriming + 100% RDN, T3: 10% HK priming + 100% RDN+ foliar application of 10% HK, T4: 10% HK priming + 75% RDN+ foliar application of 10% HK, T5: 10% HK priming + 50% RDN+ foliar application of 10% HK, T6: 10% HK priming + no Fertilizer+ foliar application of 10% HK, T7: 25% HK priming + 100% RDN+ foliar application of 10% HK, T8: 25% HK priming + 75% RDN+ foliar application of 10% HK, T9: 25% HK priming + 50% RDN+ foliar application of 10% HK, T10: 25% HK priming + no fertilizer+ foliar application of 10% HK, T11:50% HK priming + 100% RDN+ foliar application of 10% HK, T12: 50% HK priming + 75% RDN+ foliar application of 10% HK, T13: 50% HK priming + 50% RDN+ foliar application of 10% HK, T14: 50% HK priming + no fertilizer+ foliar application of 10% HK. The results revealed that T7 (128.7 cm), T2 (125.1 cm), T1 (122.6 cm), and T5 (119.9 cm) had much taller plants than the others. The highest number of grains per spike was found to in T7, T3, T2 and T8 shown at par with each other (49.90, 49.90, 48.67 and 47.67 grains/spike). Similarly, fertile spikelets per spike was shown significantly higher with T7 (23.30) which was at par with T3 and T2 (21.67 and 21.20, respectively) as compared to other treatments. The maximum grain production was seen with T7 (48.0 q/ha) and T3 (47.90 q/ha), however these two treatments were at par. Higher harvest index was observed significantly from T7, T3, T2, T12, T1 and T11 (40.6, 39.7, 39.0, 37.9, 37.8 and 37.6%, respectively) as compared with other treatments but at par with each other. The maximum α-amylase activity was observed with T7 (27.9 mg of starch hydrolyzed/g of seeds) which was at par with T3 and T2 (25.1 and 24.7 mg of starch hydrolyzed/g of seeds, respectively). From the information presented above, it can be inferred that seed priming with 10% HK along with 100% of the recommended dose of nutrients, followed by foliar applications of 10% HK at various growth stages, increased the growth, productivity and enzyme activity of late sown wheat that priming with 10% HK and its foliar application under 100% RDN increased the growth, productivity, grain quality indices, enzyme activities, and economic profitability of late-sown wheat. From the current research, it can be concluded that HK is a successful and cost-efficient method that may be utilized to increase crop production under late-sown conditions.